QUALITY IN EDUCATION: ACADEMIC EXPECTATION VS PERFORMANCE - Jusoh, Osman; Mohd Nor, Shamsida (International Business Education Journal, 2008)
Expectations are the reference point students have coming into service experience in school while perceptions reflect the service as actually received from the school. The difference or the gap between perception and expectation could be used as an indicator of the quality score in schools. Therefore the objective of this research is to collect data and information regarding expectation and perception of students towards service quality of their schools. SERVQUAL instrument has been utilized in this research. Survey has been carried out in twelve schools in the Hulu Selangor District, the middle of Malaysia. The service dimensions being used in this research are tangibility, reliability, responsiveness, assurance and empathy. Data has been analysed in order to know the level of the service quality in schools. Service shortfalls have been identified and a few suggestions have been forwarded to overcome the shortfalls. The service quality then was compared with the students’ academic performance to know the relationship between both aspects. The instrument contains sixty items altogether. Part A is regarding expectation and perception of the respondents towards their school. Part B is to identify the relative importance of each dimension of service quality while Part C is for respondents’ profile. Some modifications have been made to the statements in the SERVQUAL instrument suitable to the education field.